A PENGARUH GAYA KEPEMIMPINAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI MELALUI LOYALITAS SEBAGAI VARIABEL INTERVINING PADA KANTOR BADAN KEPEGAWAIAN DAERAH PROVINSI SULAWESI SELATAN - Jasiyah, Wa Ode Isra; Muhammadin, Akhmad; Mappamiring, Mappamiring (STIE DWI SAKTI BATURAJA, 2024)
This research aims to test and analyze the influence of Leadership Style and Organizational Culture on Employee Performance through Loyalty as an Intervining Variable at Kantor Badan Kepegawaian Daerah Provinsi Sulawesi Selatan. Data collection used primary data with questionnaire techniques whose population was obtained from Civil Servants at the South Sulawesi Province Regional Civil Service Agency Office with a random sample system totaling 49 employees. The questionnaire results have been tested using SPSS Version 26 software with instrument testing, classical assumptions and path analysis. Based on the results of the analysis, this research proves that all hypotheses are accepted, namely the first hypothesis that the Leadership Style variable has a positive and significant effect on Loyalty. Second, the Organizational Culture variable has a positive and significant effect on Loyalty. Third, the Loyalty variable has a positive and significant effect on employee performance. The four Leadership Style variables have a positive and significant effect on Employee Performance. Fifth, organizational culture has a positive and significant effect on employee performance. Sixth, leadership style has a positive and significant effect on employee performance through Loyalty as an intervining variable and Seventh, Organizational Culture has a positive and significant effect on Employee Performance through Loyalty as an intervining variable. This can prove that in general all variables are acceptable. Matching the Leadership Style, Organizational Culture, Loyalty and Employee Performance variables of Civil Servants produces optimal performance and can achieve the desired goals at the South Sulawesi Province Regional Civil Service Agency office.